EFFECT OF INTERNAL CONTROLS ON FRAUD THE DETECTION AND PREVENTION AMONG COMMERCIAL BANKS IN KENYA - KABUE, LEAH NJERI; ADUDA, DR. JOSIAH (European Journal of Business and Strategic Management, 2017)
Purpose:The study sought to investigate the effect of internal controls on fraud detection and prevention among commercial banks in Kenya. Methodology:The study adopted an explanatory research design. The population of the study wasall the 43 commercial banks operating in Kenya in the study period. The study conducted a census on all the 43 commercial banks .The study usedprimary data. An ordinary linear regression model was used. The regressions were conducted using statistical package for social sciences (SPSS) version 20. Results:The regression results indicated that there was a negative and significant relationship between reconciliation control and level of fraud prevention and detection. The results also indicated that there is a negative and significant relationship between financial governance control and level of fraud prevention and detection while the relationship between reporting and budget control and level of fraud prevention and detection was positive and significant Unique contribution to theory, practice and policy:Following the study findings, the study recommended that Commercial banks should fully reconcile their accounts more frequently in order to reduce the cases of more incidences of frauds. The study also recommends that commercial banks should put in place stronger financial governance control measures through more frequent meetings among the members of the risk management committee and also finance and investment committee. Another recommendation made by the study is that commercial banks should reduce the variances in budgets through better reporting and budgetary control measures as it will reduce cases of frauds.